Recognizing asymptomatic bacteriuria in the surveillance of catheter-associated urinary tract infections-beyond fever and positive urine culture - Hayato Mitaka; Chloe Bryson-Cahn; Jorge O. Estebane; Vanessa A. Makarewicz; John B. Lynch; Jeannie D. Chan (Cambridge University Press, 2024)
Among 143 cases of National Healthcare Safety Network (NHSN) catheter-associated urinary tract infections (CAUTI), 40% were considered catheter-associated asymptomatic bacteriuria (CA-ASB), and 18% clinical CAUTI. An alternative source of fever was present in 70% of CA-ASB. NHSN CAUTI may not be an effective metric for tracking hospital-level infection prevention efforts.